2004
DOI: 10.1016/j.eurpsy.2003.12.001
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cannabis use and schizotypal symptoms

Abstract: To test the relationship between schizotypal symptoms and cannabis use in a non-clinical population, cannabis users and non-users were asked to complete the Schizotypal Personality Questionnaire. Significant differences in scores between the groups were observed. There may be a developmental process in the relationship between cannabis use and schizotypal symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
2
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 8 publications
4
38
2
3
Order By: Relevance
“…One study found a significant positive correlation between schizotypy scores and total self-reported years of cannabis use (Skosnik et al, 2006), and another showed that in individuals reporting cannabis use, average age of onset of schizotypal symptoms preceded the age of initiation of cannabis use (Schiffman et al, 2005). Bailey and Swallow (2004) found a broader set of associations between cannabis use and the presence of positive, negative, and disorganized schizotypal characteristics among 60 6 undergraduates. However, some studies have suggested that individuals who use cannabis have lower negative schizotypal symptomatology than those not using the drug (Nunn et al, 2001;Schiffman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study found a significant positive correlation between schizotypy scores and total self-reported years of cannabis use (Skosnik et al, 2006), and another showed that in individuals reporting cannabis use, average age of onset of schizotypal symptoms preceded the age of initiation of cannabis use (Schiffman et al, 2005). Bailey and Swallow (2004) found a broader set of associations between cannabis use and the presence of positive, negative, and disorganized schizotypal characteristics among 60 6 undergraduates. However, some studies have suggested that individuals who use cannabis have lower negative schizotypal symptomatology than those not using the drug (Nunn et al, 2001;Schiffman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies involving university students have demonstrated correlations between cannabis use and positive schizotypal symptomatology in particular (Bailey & Swallow, 2004;Dumas et al, 2002;Mass, Bardong, Kindl, & Dahme, 2001;Nunn, Rizza, & Peters, 2001;Schiffman, Nakamura, Earleywine, & LaBrie, 2005;Skosnik, Krishnan, Aydt, Kuhlenshmidt, & O'Donnell, 2006). One study found a significant positive correlation between schizotypy scores and total self-reported years of cannabis use (Skosnik et al, 2006), and another showed that in individuals reporting cannabis use, average age of onset of schizotypal symptoms preceded the age of initiation of cannabis use (Schiffman et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Trabajos previos que analizan el papel de los rasgos negativos de la esquizotipia o las experiencias psicóticas negativas de tipo atenuado, encuentran resultados similares aunque inconsistentes. Por ejemplo, algunos estudios reflejan la existencia de asociación entre la dimensión negativa y el consumo a nivel subclínico (Bailey y Swallow, 2004;Davis et al, 2013); no obstante, es igualmente cierto que otros estudios hallan que los consumidores de cannabis y alcohol presentan menores puntuaciones en la dimensión negativa en comparación con los no consumidores (Nunn et al, 2001;Skosnik et al, 2008) o no encuentran tal asociación (Barkus et al, 2006;Dumas et al, 2002;Fridberg et al, 2011;Schiffman et al, 2005). En términos generales, estos resultados parecen indicar que existe un patrón de asociación diferenciado entre este conjunto de experiencias y rasgos psicóticos subclínicos y el consumo de sustancias (p.…”
Section: Discusión Y Conclusionesunclassified
“…Asimismo, estudios transversales han encontrado que los rasgos esquizotípicos son predicto-res del consumo de alcohol y tabaco en universitarios españoles (Fumero et al, 2009). En este sentido, diversos estudios indican que los consumidores de cannabis y/o alcohol presentan menores puntuaciones en la dimensión negativa de la esquizotipia en comparación con los no consumidores (Nunn et al, 2001;Skosnik, Park, Dobbs, y Gardner, 2008), si bien otros trabajos no encuentran tal asociación (Barkus et al, 2006;Dumas et al, 2002;Fridberg, Vollmer, O'Donnell, y Skosnik, 2011;Schiffman, Nakamura, Earleywine, y LaBrie, 2005), o incluso revelan una asociación positiva (Bailey y Swallow, 2004;Davis et al, 2013).…”
unclassified
“…Los tipos más frecuentes son el esquizotípico (Bailey y Swallow, 2004;Williams, Wellman y Rawlins, 1996), el trastorno antisocial (Comptom, Thomas, Conway y Colliver, 2005;Wittchen, Fröhlich, Behrendt, Günther, Rehm, Zimmerman, et al, 2007) y el trastorno límite (Chabrol, Massot y Mullet, 2004).…”
Section: Introductionunclassified